Examining the Association between Intimate Partner Violence and Suicidal Ideation among Women Living with HIV in a Low- and Middle-Income Country. Issue 9 (21st October 2021) - Jiwatram-Negrón, Tina; Meinhart, Melissa; Primbetova, Sholpan; Terlikbayeva, Assel; El-Bassel, Nabila
ABSTRACT: Intimate partner violence (IPV) and suicidality are intersecting social problems. However, limited studies have examined IPV and suicidality among socially marginalized women, such as women living with HIV (WLHIV), or in low- and middle-income countries, where social services vary widely. This paper seeks to fill this gap by exploring the association between IPV and suicidal ideation among a sample of WLHIV. A cross-sectional survey was administered to 249 WLHIV across five regions of Kazakhstan, Central Asia. Both IPV (50.2%) and suicidal ideation (40.5%) were common. Adjusted multivariate logistic regression analyses indicated critical associations between all types of IPV and suicidal ideation: verbal (a OR  = 2.5, p <.05); psychological (a OR  = 3.3, p <.01); physical (a OR  = 2.3, p <.05); sexual (a OR  = 3.6, p <.01); injurious (a OR  = 4.6, p <.01); and any IPV (a OR  = 2.3, p <.05). Consistently significant covariates included marital status, social support, injection drug use, and HIV-related stigma ( p <.05). Findings suggest a need to examine the crossover pathways and rates of IPV, HIV, and suicidality. Implications include the need for increased capacity building among providers to address these co-occurring problems through comprehensive assessments, safety planning, and linkage to care.